Cryptography Recent Advances and Future Developments - Bernardini, Riccardo (IntechOpen, 2021)
Despite being 2000 years old, cryptography is still a very active field of research. New needs and application fields, like privacy, the Internet of Things (IoT), physically unclonable functions (PUFs), post-quantum cryptography, and quantum key distribution, will keep fueling the work in this field. This book discusses quantum cryptography, lightweight cryptography for IoT, PUFs, cryptanalysis, and more. It provides a snapshot of some recent research results in the field, providing readers with some useful tools and stimulating new ideas and applications for future investigation.